CTLA-4 Polymorphisms and Systemic Lupus Erythematosus: A Comprehensive Meta-Analysis - Liu, Jie (Mary Ann Liebert, Inc., 2013)
Objective: The aim of this study was to determine whether the SNPs +49A/G and CT60A/G of the CTLA-4 gene are associated with susceptibility to systemic lupus erythematosus (SLE). Methods: The comprehensive meta-analysis for +49A/G included 1753 cases and 2279 controls, and for CT60A/G included 676 cases and 576 controls. Allelic and genotypic comparisons between cases and controls were evaluated. For +49A/G, we also subdivided it by population. Results: For +49A/G, statistically significant differences were not noted (fixed: odds ratio [OR]: 1.033, 95% confidence interval [95% CI]: 0.937–1.139; random: OR: 1.038, 95% CI: 0.907–1.188). When subdivided into Asia and Europe subgroups, it showed that this polymorphism is still not significantly associated with SLE [for Asia: (fixed: OR: 1.069, 95% CI: 0.932–1.227; random: OR: 1.055, 95% CI: 0.846–1.316); for Europe: (fixed: OR: 0.988, 95% CI: 0.842–1.161; random: OR: 1.015, 95% CI: 0.805–1.281)]. And CT60A/G also did not demonstrate significant differences with SLE (fixed: OR: 1.099, 95% CI: 0.922–1.31; random: OR: 0.918, 95% CI: 0.581–1.448). Conclusion: The results suggest that the CLTA-4 gene was not associated with SLE. Further investigations are required to identify whether other at-risk polymorphisms within CTLA-4 confer a risk of SLE and to clarify the role of the CTLA-4 gene.